2019
DOI: 10.1144/jgs2019-017
|View full text |Cite
|
Sign up to set email alerts
|

The Neoarchean Uyea Gneiss Complex, Shetland: an onshore fragment of the Rae Craton on the European Plate

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Inverian and Laxfordian events). This confirms that the Lancaster basement belongs to the Neoarchean rocks of the Faroe-Shetland Terrane, which can be correlated with the similar age Central Greenland-Rae Craton on the NW side of the North Atlantic (Holdsworth et al 2018;Kinny et al 2019).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Inverian and Laxfordian events). This confirms that the Lancaster basement belongs to the Neoarchean rocks of the Faroe-Shetland Terrane, which can be correlated with the similar age Central Greenland-Rae Craton on the NW side of the North Atlantic (Holdsworth et al 2018;Kinny et al 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Previous researchers were unable to identify any definitive evidence for anything other than amphibolite-facies regional metamorphism in the rather sparse set of Faroe-Shetland Terrane basement samples and so it was suggested that the Neoarchean ages obtained dated primary crystallization of the igneous protoliths. Younger zircon rims formed c. 2700-2710 Ma in both areas were thought to possibly date the age of deformation and amphibolitefacies regional metamorphism (Kinny et al 2019). It is significant that similar aged rims are also recognized in the Lancaster samples (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Neoarchaean orthogneisses of broadly similar composition and age extend north of the Scottish mainland at least as far as the northernmost tip of Shetland (Holdsworth et al 2018;Kinny et al 2019). Equivalent units underlie much of the Faroe-Shetland basin and the ca 200km Rona Ridge, as shown by analyses of basement-penetrating offshore cores (Fig 1; see Ritchie et al 2011).…”
Section: Location and Regional Structurementioning
confidence: 93%
“…Lewisian Gneiss Complex of the Hebridean Terrane of mainland Scotland (Pringle 1970;Flinn et al 1979;Flinn 1988; however, see also Holdsworth et al 2019;Kinny et al 2019). Structurally overlying the Neoarchean Uyea Gneiss Complex is the metasedimentary Sand Voe Group that has been correlated with the early Neoproterozoic Moine Supergroup of the Northern Highlands Terrane (Flinn 1988).…”
Section: Accepted Manuscriptmentioning
confidence: 99%